The Problematic Nature of Fibromyalgia Diagnosis in the Community. Issue 1 (15th March 2019) - Srinivasan, Sachin; Maloney, Eamon; Wright, Brynn; Kennedy, Michael; Kallail, K. James; Rasker, Johannes J.; Häuser, Winfried; Wolfe, Frederick
Abstract : Background: Recently, some studies suggested that clinical diagnosis of fibromyalgia is inaccurate and does not reflect current definitions. However, this hypothesis has not been tested. We examined whether fibromyalgia was accurately diagnosed in the community. Methods: We surveyed 3276 primary care patients to determine current fibromyalgia status by criteria (CritFM). We also determined whether the patients had a physician's diagnosis of fibromyalgia (MDFM) and the level of symptom severity as measured by the polysymptomatic distress scale (PSD). Results: The prevalence of MDFM and CritFM was 6.1% (95% confidence interval [CI] 5.3%, 6.9%) and 5.5% (95% CI 4.8%, 6.3%), respectively. However, only 32.2% with MDFM met 2016 criteria (CritFM), and only 35.4% with CritFM also had MDFM. The kappa statistic for diagnostic agreement was 0.296 (minimal agreement). The mean PSD score was 12.4 and 18.4 in MDFM and CritFM, respectively. The odds ratio for being a woman compared with being a man was 3.2 for MDFM versus 1.9 for CritFM, P = 0.023. Of the patients with MDFM, 68.3% received specific fibromyalgia pharmacotherapy. Conclusions: There is little agreement between MDFM and CritFM. Only one‐third of MDFM satisfy fibromyalgia criteria, and only one‐third of patients who meet the criteria have a clinical diagnosis of fibromyalgia. Physician diagnosis is biased and more likely in women. Fibromyalgia treatment is common in MDFM (70.7%). Overall, MDFM appears subjective and unrelated to fibromyalgia criteria. There appears to be no common definition of fibromyalgia in the community.